A practical tool for selecting microalgal species for biodiesel production - Martín, L. A. (2020)
In the search for energy sources to replace fossil fuels, microalgae have shown promising characteristics. Their cultures have several advantages over the conventional crops used for commercial biodiesel: they have fast growth rates and a high lipid content and can grow in environments unfit for agriculture. However, relatively few species have so far been studied as biodiesel feedstock. In order to facilitate the search for potentially useful species/strains, in this work, a bioprospecting tool based on biomass and oil production process requirements, triacylglyceride content, and biodiesel properties has been developed. For this purpose, an overall score (OS) was proposed as a tool based on biological, economic, and environmental factors. By applying the OS to nine species, we were able to narrow down the number of species within the diatom group, which are potentially suitable for large-scale biodiesel production. Halamphora coffeaeformis, Navicula cincta, and N. gregaria were the species with the highest OS (1.65-1.5). It is expected that this tool will provide a useful contribution to the criteria applied in the selection of microalgal species for large-scale biodiesel production.